Plasma level of lipocalin 2 is increased in neovascular age-related macular degeneration patients, particularly those with macular fibrosis - Mei Chen; Nan Yang; Judith Lechner; Levente Toth; Ruth Hogg; Giuliana Silvestri; Usha Chakravarthy; Heping Xu (Immunity & Ageing, 2020)
Abstract Background Previously, we and others have reported higher populations of circulating neutrophils in patients with neovascular age-related macular degeneration (nAMD). Neutrophil gelatinase-associated lipocalin (NGAL, also known as lipocalin-2, LCN2), an important innate immune mediator, is known to be critically involved in sterile inflammation-mediated organ failure, fibrosis, cancer progression and retinal degeneration. This study investigated the plasma levels of LCN2, matrix metalloproteinase 9 (MMP9) and LCN2/MMP9 complex in different types of nAMD and examined whether the levels were related to patients’ responsiveness to anti-VEGF therapy. Results One hundred and seventy-four nAMD patients, including 108 with choroidal neovascularisation (CNV), 32 with retinal angiomatous proliferation (RAP), 23 with polypoidal choroidal vasculopathy (PCV) and 11 unclassified patients, and 43 healthy controls were recruited to this case-control study. Fifty-eight nAMD patients had macular fibrosis and 110 patients did not. Out of the 174 nAMD patients, 80 patients responded completely, 90 responded partially, and 4 did not respond to the anti-VEGF therapy. The plasma levels of LCN2 in nAMD patients (181.46 ± 73.62 ng/ml) was significantly higher than that in healthy controls (152.24 ± 49.55 ng/ml, P = 0.047). However, the difference disappeared after adjusting for age. A positive correlation between plasma level of LCN2 and age was observed in nAMD patients (r = 0.29, P = 0.0002) but not in healthy controls. The plasma level of LCN2 was also positively correlated with circulating neutrophils in nAMD patients (r = 0.34, p = 0.0007) but not in healthy controls (r = 0.057, p = 0.77). No correlation was observed between age and circulating neutrophils. Further analysis of nAMD subtypes uncovered a significantly higher level of LCN2 in patients with macular fibrosis even after adjusting for age. No relationship was observed between plasma levels of LCN2 and patients’ responsiveness to anti-VEGF therapy. The plasma levels of MMP9 and LCN2/MMP9 complex were comparable between nAMD and controls. Conclusions Our results suggest that higher plasma levels of LCN2 in nAMD are related to ageing and increased population of circulating neutrophils. Our results also suggest that higher levels of LCN2 may increase the risk of macular fibrosis in nAMD.